UPAYA MENINGKATKAN KEMAMPUAN MEMBACA PERMULAAN DAN MOTIVASI SISWA DENGAN MODEL WORD SQUARE PADA PEMBELAJARAN BAHASA INDONESIA KELAS III SEKOLAH DASAR - Nisfa, Lala Lailatun; Fatkhiyani, Kiki; Dewi, Ririn Andriani Kumala (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze efforts to improve students' initial reading skills and motivation with the word square model in Indonesian language learning for grade III elementary school. The background of this study is the importance of initial reading skills and motivation in students. The word square learning model is considered a suitable model to improve students' initial reading skills and motivation. This study uses the classroom action research (CAR) method. Data were collected through observation sheets, written tests, oral tests of early reading skills, and questionnaires given to grade III students of UPTD SDN 4 Benda Karangampel. The results of the study showed an increase. This is evidenced by the teacher's observation score in cycle I at 83% in the very good category, cycle II 89% in the very good category, cycle III 97% in the very good category. This is a written test of students' initial reading ability in cycle I, 100% of students have not completed it from 26 students, cycle II 88% of the 23 students who completed the test had scores above the KKM and 12% of the 3 students who had not completed the test, cycle III 100% of students are compact and have understood from 26 students. Furthermore, the oral test cycle I 78% is categorized as good, cycle II 88% is categorized as very good, cycle III 96% is categorized as very good. Furthermore, students' motivation in cycle I was 76% in the good category, cycle II was 79% in the good category, cycle III was 88% in the very good category. Based on the results of this study, it can be concluded that the word square learning model can improve students' initial reading skills and motivation in Indonesian language lessons in grade III of elementary school.